Variothermal Foam Injection Molding - Dimensional Stability with High Surface Quality. Issue 3 (May 2017) - Hopmann, Christian; Lammert, Nicolai; Zhang, Yuxiao
Thermoplastic foam injection moulding offers various advantages for both processing and product design. Despite its many benefits, the moderate surface quality still constitutes a major disadvantage of this process. The mould temperature can be controlled dynamically to improve the surface quality. Different dynamic temperature control strategies are employed and analysed regarding their effectiveness and scope of application. Mould temperatures above the specific material transition temperatures allow the surface defects to be cured and enable the production of foamed thermoplastic parts with surface qualities comparable to those of the compact reference samples. The high mould temperatures during the injection phase alter the foam structure and the skin layer thicknesses, which impacts the mechanical properties.